Annual Review of Cybertherapy and Telemedicine 2014 : Positive Change: Connecting the Virtual and the Real - Wiederhold, B. K.; Riva, Giuseppe (Studies in health technology and informatics ;, 2014)
The evolution of healthcare delivery systems has included an increased reliance on technology. There has been a significant shift in the nature of care prevention, diagnosis and treatment, which has decreased the importance of traditional methods of care delivery. Cybertherapy has started to make progress in treating a variety of disorders, but more work is needed in a number of areas, including the development of easy-to-use and more affordable hardware and software and objective measurement tools, the need to address potential side-effects, and the implementation of more controlled studies t.